The characteristics of TAG and EPA accumulation in Nannochloropsis oceanica IMET1 under different nitrogen supply regimes - Meng, Y.; Jiang, J.; Wang, H.; Cao, X.; Xue, S.; Yang, Q.; Wang, W.
The strategy of nitrogen limitation has been widely applied to enhance lipid production in microalgae. The changes of cellular composition, and the characteristics of triacylglycerol (TAG)and eicosapentaenoic acid (EPA)accumulation in Nannochloropsis oceanica IMET1 were investigated. The results revealed that after nitrogen limitation TAG rather than carbohydrate was the dominant carbon sink in N. oceanica IMET1. Different nitrogen supplementation strategies were applied in order to achieve high TAG and EPA productivity, respectively. Limited nitrogen was supplied to improve TAG production, and a maximum productivity of 29.44 mg L?1 d?1 was obtained, which was a 6.74-fold increase compared to nitrogen-depleted cultivation. The highest EPA productivity of 7.66 mg L?1 d?1 was achieved under nitrogen-replete cultivation, which is different from the condition for TAG maximum productivity because the EPA is in glycolipids and phospholipids mainly. The fatty acid composition analysis identified the source of acyl group in TAG accumulation.
Keywords: NANNOCHLOROPSIS OCEANICA IMET1; TAG; EPA; NITROGEN LIMITATION; FATTY ACID COMPOSITION